The Influence of Gender Roles and the Female Workforce on income and Economic Growth in East Kalimantan - Ari Kesuma Dewi; Eny Rochaida; Rahcmad Budi Suharto (International Journal of Management Research and Economics, 2024)
The purpose of this study was to determine the effect of The Influence of Gender Roles and the Female Workforce on Poverty and Economic Growth in East Kalimantan. The data used is secondary time series data for 2012 – 2022 obtained from BPS East Kalimantan Province. Using the SPSS 25 analysis tool with the path analysis method, this research concludes that gender roles have no effect on poverty, while gender roles have an influence on economic growth. Labor has an influence on poverty and also economic growth, meanwhile poverty has an influence on economic growth. The role of gender on economic growth through poverty has an influence, while labor on economic growth through poverty does not have a significant influence.